PENDIDIKAN KESEHATAN DALAM MENINGKATKAN PENGETAHUAN, SIKAiP, DAN PERILAKU TERHADAP MEROKOK PADA REMAJA DI SMP NEGERI BANDA ACEH - , Nurhayati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Indonesia is the fifth biggest country in cigarette consumption worldwide. There is 1.2 billion world population that smoke or about 1/3 of world population above 15 years old smoke, whereas loss due to smoking reaches 200 billion US dollar and around 100 billion US dollar happens in developing countries. Furthermore, 29.7% of Aceh children over ten years old are active smokers. Objective: The study aimed to evaluate the impact of health education through lecture and discussion to knowledge, attitude and behavior of smoking among teenagers at public junior high school of Banda Aceh. Method: The study was a quasi experiment that used non randomized pre test and post test with control design involving 70 students and they were divided into two groups. The experiment group consisted of 35 students and the control group 35 students. Trial of questionnaire was made prior to the study. Samples were purposively taken. Data analysis used paired ttest and independent t-test. Hypothesis test was based on significant level of p < 0.05. Result: There was an increasing of knowledge, attitude and behavior of respondents on smoking in experimental group. This could be seen after one month of intervention